Impulsive Buying Driven by E-WOM with Influencers as a Mediator on TikTok - Wandini Rohmatin Sariyani; Nurhasan, Rohimat; Wufron (Forum Kerjasama Pendidikan Tinggi, 2025)
This examination seeks to explore the effect of e-Wom on hasty purchasing behavior, using marketing influencers acting serving as a mediator in the relationship among active TikTok users from Generation Z in Indonesia. The research adopted a quantitative survey. The method involved distributing questionnaires. structured questionnaires to 400 respondents. The data gathered were examined through the PLS-SEM approach method. The results reveal that eWOM positively influences impulsive buying with a path coefficient value of 0.888 and a significance level of less than 0.005, as well as on marketing influencers with a coefficient value of 0.921. marketing influencers have also been demonstrated to exert a positive influence on impulsive buying with a coefficient of 0.696. The mediating role of influencers in the relationship between e-WOM and impulsive buying is also confirmed through indirect effect analysis. These findings highlight the strategic relevance of employing eWOM and leveraging influencer engagement in digital marketing to shape impulsive buying behavior in social media environments.These findings support marketing practitioners in crafting more impactful campaigns, while also adding to the organism of academic research finding in the areas of consumer behavior and digital promotion.